Impacto da Desoneraç\~ao da Folha de Pagamento sobre o emprego: Novas evidências - Felipe Garcia; Adolfo Sachsida; Alexandre Ywata de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– We use data from the period 2009-15 to estimate the impact of the public policy aiming to decrease the taxes paid by companies over their payroll. The objective of this program, so called Less Taxes on the Payroll ("Desoneraç\~ao da Folha de Pagamento"), was to burst the employment in the firms benefited by the tax cut. Overall our econometric results show no employment effect of this program.
Keywords: C32; D04; 330; tax cut; employment; payroll taxes; public program evaluation; difference in difference